Causes and consequences of cultural and historical manor landscape fragmentation in the 19th - 21st century Latvia - Bāra, Lelde; Ziemeļniece, Aija (Landscape Architecture and Art, 2021)
In the post-war years (50s-80s of the 20th century), the legislation of the Soviet Union defined that the list of monuments to be protected by the state is deemed a political document with ideological significance. Due to this reason, the list of architectural monuments was subject to politically motivated manipulations not only during Stalin's time, but also later. The political situation after the occupation in 1940 required to adapt to the sovietization demands, didactically dividing cultural monuments into “progressive” and “bourgeois” or those unfit for socialist construction. The history of the cultural heritage protection measures has been related to politics. With the growing importance of cultural heritage in the formation of historical memory, the protection and promotion of monuments becomes an essential part of the ideology of nation states. A change in the state power means a change in the dominant political ideology, which affects the work of state institutions in the protection of cultural heritage. The research topic has an interdisciplinary nature with the intertwining of political, economic and social aspects. The cultural heritage includes the political dimension and its role in shaping national identity models. The rise of the Duchy of Courland in the first half of the 18th century made a serious contribution to the landscape of the Lielupe left bank basin in the Zemgale region. The landscape of the both historical ensembles of Svete and Vircava manors was disturbed (fragmented) by the economic and political position of the state. The basis for that was bringing new infrastructure in the nature. As a result of political, economic and social pressures, the landscapes of cultural and historical manors have, over the centuries, fragmented and transformed the use of the original structure and functional landscape. The aim of the research is to identify and emphasize the causes and consequences of the fragmentation of the cultural and historical landscape of manors.